PENAS XVI PETANI DAN NELAYAN DI PADANG UPAYA KONSOLIDASI DARI ANCAMAN KRISIS PANGAN - Saodin (MUHKAL, 2023)
PENAS Farmer Fisherman Activities XVI Year 2023 will be held at the Sutan Sjahrir Air Force Base, Jalan Prof. Dr. Hamka Parupuk Tabing, Koto Tangah District, Padang City, West Sumatra Province. PENAS Farmer Fishermen XVI Year 2023 based on the results of the Main Discussion of the National Mainstay Farmer Fishermen Contact Group (KTNA) at PENAS Farmer Fishermen XV 2017 in Aceh, it was agreed that PENAS Farmer Fishermen XVI Year 2023 will be held in West Sumatra. Letter of the Secretary General of the Ministry of Agriculture of the Republic of Indonesia Number: B-842/B150/A/03/2022 dated 7 March 2022 Regarding: Implementation of PENAS XVI Activities, which explains that the National Fishermen Farmer Week (PENAS) XVI will be held on 10 –15 June 2023. PENAS Fishermen Farmers is a meeting forum or place for teaching and learning activities, exchanging information and experiences between farmers –fishers and forests, researchers, extension workers, the private sector, and the government so as to generate enthusiasm and responsibility, as well as independence for farmers fishers and forests as actors majoring in the Development of Agriculture, Fisheries and Forestry. Increasing the motivation and enthusiasm of farmer fishermen and forest farmers as well as agribusiness communities in developing competitive, populist, sustainable agribusiness systems and businesses through mutually beneficial partnerships. In accordance with the theme of PENAS XVI Farmer Fishermen 2023 is Strengthening Potential and Bargaining Position of Local Commodities to Realize Sustainable Food Self Sufficiency Towards Indonesia World Food Barn 2045.